A Self-Stabilizing Leader Election Algorithm in Highly Dynamic Ad Hoc Mobile Networks - Derhab, A.; Badache, N. (IEEE transactions on parallel and distributed systems, 2008)
The classical definition of a self-stabilizing algorithm assumes generally that there are no faults in the system long enough for the algorithm to stabilize. Such an assumption cannot be applied to ad hoc mobile networks characterized by their highly dynamic topology. In this paper, we propose a self-stabilizing leader election algorithm that can tolerate multiple concurrent topological changes. By introducing the time-interval-based computation concept, the algorithm ensures that a network partition can within a finite time converge to a legitimate state even if topological changes occur during the convergence time. Our simulation results show that our algorithm can ensure that each node has a leader over 99 percent of the time. We also give an upper bound on the frequency at which network components merge to guarantee the convergence.